Individual and Family Development, Health, and Well-being - Lang, Diana; Cone, Nicholas (Open textbook library., 2022)
This book provides an overview of lifespan developmental tasks (physical, cognitive, language, social, emotional) examined from individual and family theoretical perspectives. It covers topics related to families, diversity, individual and family health and well-being, and reciprocal relationships as affected by external factors.